2022
DOI: 10.1186/s12903-022-02133-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of telemedicine for symptoms management in oral medicine: a retrospective observational study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 has had devastating effect on access to care in many specialties and dental services including oral medicine. Following the shelter‐in‐place orders in March 2020, we implemented Tele(oral)medicine practices for the diagnosis and management of some oral medicine conditions. Objectives To assess the role of telemedicine visits with respect to managing pain among patients affected by oral dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Additionally, teledentistry could be used to monitor and follow up on patients. Alsafwani et al ( 54 ) reported that 65% of patients got a median improvement in oral pain after being consulted via teledentistry during the COVID-19 pandemic. Morishita et al ( 55 ) reported that teledentistry could help patients get dental services and dental care for the first visit and a follow-up visit in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, teledentistry could be used to monitor and follow up on patients. Alsafwani et al ( 54 ) reported that 65% of patients got a median improvement in oral pain after being consulted via teledentistry during the COVID-19 pandemic. Morishita et al ( 55 ) reported that teledentistry could help patients get dental services and dental care for the first visit and a follow-up visit in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to focusing on speeding up elective procedures, collective preventive actions such as smoking control, self-care and oral health prevention, with oral health monitoring for these groups. [34][35][36] A study by Aquilanti, identified that the use of teleodontology immediately after reopening, to screen patients, was an effective way of minimizing damage and waiting times for care. 37 It speeds up the treatment of patients who are identified as having diseases that need more urgent care, such as oral cancer.…”
Section: Immediate Solutions To Tackle the High Demand For Dental Carementioning
confidence: 99%
“…Live consultations provided patients with the opportunity to interact with clinicians in real time, while in the store-and-forward option, patients provided photos, videos, texts, or voice messages that allowed clinicians to evaluate a patient's concern at a convenient time and the ability to share images or radiographs with colleagues [5,[16][17][18][19][20][21][22][23][24][25]. Radiographs used for teledentistry visits were prepandemic radiographs, and the inability to obtain new or additional images via virtual appointments was noted as a barrier to teledentistry [17,26]. If new or additional radiographs were required, patients scheduled an in-person visit for radiographic imaging [20,23].…”
Section: How Was Teledentistry Implemented During the Covid-19 Pandemic?mentioning
confidence: 99%
“…The second recurrent item category was the type of applications and programs used to implement teledentistry. The most mentioned applications were WhatsApp, Skype, Zoom, and Google-related services [16,17,19,24,[26][27][28][29][30][31][32][33][34][35]. Less common were Mobile Mouth Screening Anywhere, a program specifically designed to detect oral cancer via photos uploaded by patients; a video platform called Video 4 Health used in conjunction with a teletrailer program, Telegram; Attend Anywhere; Facetime; and Health Insurance Portability and Accountability Act (HIPAA)-compliant programs such as Mailgate SC, Doxy.me, WebEx, Virtru, MD Office Mail, and LuxSci [5,27,36,37].…”
Section: How Was Teledentistry Implemented During the Covid-19 Pandemic?mentioning
confidence: 99%
See 1 more Smart Citation